Task-shifting of orthopaedic surgery to non-physician clinicians in Malawi: effective and safe? - Wilhelm, Torsten (Tropical doctor, 2017)
There is a shortage of orthopaedic surgeons in Malawi. Orthopaedic clinical officers (OCOs) treat trauma patients and occasionally perform major orthopaedic surgery. No studies have assessed the efficacy and safety of their work. The aim of this study was to evaluate their contribution to major orthopaedic surgery at Zomba Central Hospital. Data about orthopaedic procedures during 2006-2010 were collected from theatre books. We selected major amputations and open reductions and plating for outcome analysis and collected details from files. We compared patients operated by OCOs alone (‘OCOs alone’ group) and by surgeons or OCOs assisted by surgeons (‘Surgeon present’ group). OCOs performed 463/1010 major (45.8%) and 1600/1765 minor operations (90.7%) alone. There was no difference in perioperative outcome between both groups. OCOs carry out a large proportion of orthopaedic procedures with good clinical results. Shifting of clinical tasks including major orthopaedic surgery can be safe. Further prospective studies are recommended.